Amyotrophic lateral sclerosis: glutamate dehydrogenase and transmitter amino acids in the spinal cord. Issue 11 (November 1991) - Malessa, S; Leigh, P N; Bertel, O; Sluga, E; Hornykiewicz, O
Abstract : Measurements were taken of the activity of glutamate dehydrogenase (GDH) and the levels of transmitter amino acids in anatomically dissected regions of cervical and lumbar spinal cord in eight patients dying with amyotrophic lateral sclerosis (ALS) and in 11 neurologically normal controls. GDH activity was considerably increased in lateral and ventral white matter and in the dorsal horn of the ALS cervical spinal cord, but normal in the ventral horn and the dorsal columns. Similar, although less pronounced, GDH changes were found in the lumbar enlargement. The mean concentrations of aspartate and glutamate were reduced in all regions of ALS spinal cord investigated. Taurine concentrations were significantly increased in several subdivisions of cervical spinal cord, but normal in lumbar regions. Glycine levels were significantly reduced in lumbar ventral and dorsal horns. There was no striking change in spinal cord GABA levels in our ALS patients. It is suggested that the reduced levels of glutamate and aspartate as well as the elevated GDH activity in the spinal cord of ALS patients may reflect an overactivity of the neurons releasing these potentially excitotoxic amino acids and thus may be causally related to the spinal neuro-degenerative changes characteristic of ALS.